Laporan Kasus: Kandidiasis Akut Eritematous pada Penderita Diabetes Melitus - Aris Aji Kurniawan; Tirta Wardana; Arif Rachman Darmawan (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2018)
Oral Candidiasis is infectious that caused by fungi Candida albican. Candida infection can happen on Diabetes mellitus patients (DM) because of glucose high level on oral cavity fluid and decreasing immunity patient. The purpose was to discuss and management acute erythematous candidiasis on DM patient. A 63-year-old male patient arrives at the Dental Hospital with dorsal pain, heat and pain when eating and drinking. Pain has been felt since about 2 months ago after the patient experienced heart disease. The patient has a history of controlled diabetes mellitus, controlled hypertension, asthma and gastritis. The patient feels pain in his tongue getting worse accompanied by a burning sensation and pain when the body was unhealthy. The patient was diagnosed with acute erythematous candidiasis and treated with systemic antifungal, mouthwash and topical antiseptic for oral cavity cases and was referred to an internal medicine specialist for blood sugar control. The patient was declared cured after 36 days of treatment. Knowing the predisposing factors in this case (DM) is very important in the management of erythematous acute candidiasis therapy. Patients with diabetes mellitus must routinely control blood glucose levels, maintain oral hygiene and not worsen by adding other predisposing factors.